MICROSCOPIC EXAMINATION OF OVINE BABESIOSIS AT BAGHDAD CITY / IRAQ - K. , Arwa R.; Kawan , M. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted to detect the prevalence of Babesiosis in different areas at Baghdad city, by using microscopic examination ;180 sheep’s head blood samples were collected from each local breed (122 males and 58 females) with different age groups from 6 months to more than one year old, during the period extended from 1/October2019 to end of April 2020.Giemsa stained blood smears were done for detection Babesia spp. ; The overall rate of infection with Babesia spp. in sheep was 15.55% (28/180), significant differences P≤0.05 was recorded between male 19.67% ( 24/122) and female 6.89% ( 4/58 ), and sheep with equal or more than one year old registered higher rate of infection 18.18% (2/11) , also highest rate of infection recorded in April 45% (9/20) with highly significant differences P≤0.01 between months of study.